2013
DOI: 10.1590/s1806-83242013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among oral habits, orofacial function and oral health-related quality of life in children

Abstract: Abstract:The objective was to evaluate the relationship among oral habits, oral function and oral health-related quality of life (OHRQoL) in children. Three hundred and twenty-eight subjects (8-14 years old) were assessed for orofacial function using the Brazilian version of the Nordic Orofacial Test-Screening (NOT-S). OHRQoL was assessed using the Child Perceptions Questionnaires (Brazilian versions) for the 8-10 (CPQ 8-10 ) and 11-14 (CPQ 11-14 ) year age groups. The subjects were distributed into a Habit gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
5
19
1
1
Order By: Relevance
“…The results of the questionnaire in this study support the statements of Peres et al (2011) that occlusal findings and speech capability (as well as chewing capability and reports of pain) are important dimensions of oral health perception. The outcomes of the present study are also in line with the general findings of Bakke et al (2007) and Leme et al (2013), who report that the presence of orofacial dysfunctions is related to decreased well-being and decreased quality of life. (Pena-Brooks and Hedge, 2000) in children seeking orthodontic treatment (n = 56) and in children without further orthodontic treatment (n = 54).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the questionnaire in this study support the statements of Peres et al (2011) that occlusal findings and speech capability (as well as chewing capability and reports of pain) are important dimensions of oral health perception. The outcomes of the present study are also in line with the general findings of Bakke et al (2007) and Leme et al (2013), who report that the presence of orofacial dysfunctions is related to decreased well-being and decreased quality of life. (Pena-Brooks and Hedge, 2000) in children seeking orthodontic treatment (n = 56) and in children without further orthodontic treatment (n = 54).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, /s/ and /t/ findings were the most frequent sound error across languages as well. [6][7][8][9][10][11][12][13] In a study by Leavy et al, 16 lingual protrusion was found to be the most common visual inaccuracy among patients with malocclusions. As Subtelny and coworkers 17 noted, the articulatory error of /s/can be a result of excessive fronting of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Such studies have described a transient effect, with acquired errors resolved within 2 to 3 months. [2][3][4]14 The phonemes acknowledged to present lingering difficulties with articulation are /s/, /f/, /v/, /t/, /r/, /n/, and /l/ phonemes.…”
Section: Introductionmentioning
confidence: 99%
“…These structures interact with one another to carry out oro‐facial functions, such as mastication, respiration, swallowing, articulation and facial expression . Some pathologies, traumas and parafunctional habits can affect these functions, causing oro‐facial dysfunction or temporomandibular disorders (TMDs) .…”
Section: Introductionmentioning
confidence: 99%